ARCHITECTURAL ASPECTS OF INTERIOR SYSTEMS IN ADAPTIVE INDUSTRIAL BUILDINGS - Kovachev, Atanas; Asparuhov, Stefan (E-Journal VFU, 2026)
This article examines the systemic aspects of interior finishing in industrial architecture as a primary factor for achieving spatial flexibility and operational sustainability. In the context of accelerated technological cycles, the study analyzes the synergy between the classical Bulgarian school of industrial interior design (Kostov, Pisarski) and modern European factory planning methodologies (Wiendahl, Pottgiesser, König, etc.). The architectural parameters of industrial floors as installation platforms, modular partition systems, and technical ceilings are examined in detail through the "building within a building" concept. Special attention is paid to the ergonomics of vertical communications and the humanization of the work environment through the integration of hybrid recreational spaces. Conclusions are drawn regarding the role of interior components as a tool for extending the life cycle of industrial facilities and enhancing their competitiveness.